Validation protocol for current good manufacturing practices production of [15O]water for hybrid PET/MR studies. Issue 10 (October 2020) - Cockburn, Neil; Corsaut, Jeffrey; Kovacs, Michael S.; St. Lawrence, Keith; Hicks, Justin W.
Abstract : Introduction: Oxygen-15 ( 15 O; t½ = 122.4 s) has been used for nuclear imaging experiments since the beginning of the field. With the advent of simultaneous hybrid PET/MR technology, [ 15 O]water has seen a resurgence and remains the gold standard method for quantitative blood flow studies. The short half-life presents a nontrivial challenge to applying current good manufacturing practices production methods to maintain patient safety. Methods: A two-vial production method was devised to ensure adequate mixing of [ 15 O]water vapour into buffered isotonic saline. For production validation, six batches of [ 15 O]water were prepared: sterility, quality control testing and four patient doses. The final dose also underwent quality tested. Routine quality control testing included the following: radiochemical identity and purity, radionuclidic identity and purity, appearance, pH, pyrogenicity, and filter integrity. Sterility was retrospectively confirmed. For validation, breakthrough Pt concentration was also measured. Results: Consistent yields of 10–12 GBq (270–325 mCi) were obtained 3 min after bombardment. Overall, 26 [ 15 O]water batches underwent quality control testing under this protocol and all met or exceeded release specifications for clinical use. Conclusion: The multiple batch protocol proved to be a safe and effective means for producing [ 15 O]water. Furthermore, this protocol could be readily adapted by any facility attempting to produce [ 15 O]water for clinical studies. Compared with previous attempts at our site, the protocol outlined here was more consistent and reliable, improved production workflow and led to more available radioactivity for participant injection and QC testing.